Pelatihan Pengembangan Kemampuan Bahasa Inggris Secara Kontekstual Dengan Penerapan TPR - Wariyati Wariyati; Sujarwo Sujarwo; Azhary Tambusai; Yugi Diraga Prawiyata (LPPI UMN AL WASHLIYAH, 2024)
Competence in responding in English communication is a fundamental ability. The principle of English communication is that it is balanced according to individual needs, open spoken language, takes place in a curriculum and has diversity. The basic principles of acceptable English communication include 3 points, namely contextual, in line with scope and responsive. Context-based English speaking training trains teachers to teach English not just language knowledge, but also includes balanced cognitive and psychomotor skills. This service activity has become a solution to students' low basic skills in communicating using foreign languages. The implementation methods used to solve partners' priority problems are focus group discussions (FGD), training and mentoring, teaching simulations for implementing TPR and basic English based on contextual purpose, speaking tests based on context for students. The teachers were very enthusiastic after participating in this training and it became easier to modify English learning for elementary school students in a more natural and applied way.